Evaluation of hepatitis C testing in men who have sex with men, and associated risk behaviours, in Manchester, UK. (27th January 2017) - Ireland, G; Higgins, S; Goorney, B; Ward, C; Ahmad, S; Stewart, C; Simmons, R; Lattimore, S; Lee, V
Abstract : Objective: To determine the prevalence of newly diagnosed hepatitis C virus (HCV) and associated risk behaviours among men who have sex with men (MSM) in Manchester. Method: A survey among MSM attending four genitourinary medicine clinics in Manchester was carried out over 9 months in 2013. Participants were asked about recent sexual behaviour, recreational drug use and HIV status. All men were offered an HCV test. Results: Overall, 2030 MSM completed a questionnaire and accepted an HCV test. Of whom, 0.9% (18) were newly diagnosed with HCV, including 1.8% (13/735) of HIV-positive MSM, 0.7% (3/440) of MSM of unknown HIV status and 0.2% (2/855) of HIV-negative MSM. HCV positivity was significantly associated with HIV status (p<0.001). When compared with HIV-negative MSM, HIV-positive MSM had higher rates of sharing snorting drug equipment, injecting drugs/'slamming' and using recreational drugs (all p<0.05) but lower rates of five or more sexual partners and insertive unprotected anal intercourse (p<0.05). MSM newly diagnosed with HCV had significantly higher prevalence of unprotected sex, sex with someone HCV positive, fisting, group sex, ever injecting drugs/'slamming' and recreational drug use (p<0.002). Conclusions: In this survey, HIV-positive MSM had significantly different drug use behaviour which may explain the higher HCV burden. However, HCV was also associated with HIV-negative MSM engaging in high-risk sexual practices. All MSM attending sexual health clinics must have a risk assessment and HCV screening should be offered based on the risk. Further studies are warranted to explore the interplay between HCV and HIV risk associated with drug use versus sexual practices.